Spatial Variation of Seismicity in Central Himalayan Region - Adhikari, Bhesha Raj; Paudyal, H. (Himalayan Physics, 2015)
Spatial variation of seismicity in Central Himalayan Region for the period 1964 to 2008 has been studied. Seismic activity is highly concentrated in western Nepal, fairly scattered in central Nepal and concentrated in south-eastern Nepal where the activity offset towards North from major faults. The Himalayan Physics Year 5, Vol. 5, Kartik 2071 (Nov 2014) Page : 47-50